2014
DOI: 10.1002/jbm.a.35206
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral regeneration using an oriented nanofiber yarn‐collagen type I/hyaluronate hybrid/TCP biphasic scaffold

Abstract: Osteochondral defects affect both the articular cartilage and the underlying subchondral bone, but poor osteochondral regeneration is still a daunting challenge. Although the tissue engineering technology provides a promising approach for osteochondral repair, an ideal biphasic scaffold is in high demand with regards to proper biomechanical strength. In this study, an oriented poly(l-lacticacid)-co-poly(ε-caprolactone) P(LLA-CL)/collagen type I(Col-I) nanofiber yarn mesh, fabricated by dynamic liquid electrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
(53 reference statements)
0
37
0
4
Order By: Relevance
“…In our previous research, we showed the importance of SHP‐2 function for controlling normal hematopoiesis . The excellent degradability and bioactivity properties of β‐tricalcium phosphate (β‐TCP) have also been shown in our previous research . BMSCs are frequently used as a cell source for bone tissue engineering because of their multipotency, relative abundance and rapid expansion .…”
Section: Introductionmentioning
confidence: 85%
“…In our previous research, we showed the importance of SHP‐2 function for controlling normal hematopoiesis . The excellent degradability and bioactivity properties of β‐tricalcium phosphate (β‐TCP) have also been shown in our previous research . BMSCs are frequently used as a cell source for bone tissue engineering because of their multipotency, relative abundance and rapid expansion .…”
Section: Introductionmentioning
confidence: 85%
“…Collagen is easily degraded and absorbed by human body, leading to good attachment to cells, although it has less mechanical strength ( E ∼ 100 MPa) than bone ( E ∼ 2 GPa) . Therefore, collagen is often utilized as a composite material and blended with other materials such as ceramics (hydroxypatite, β‐tricalcium phosphate) and various synthetic polymers (polycaprolactone, polylactic acid, and polyglycolic acid) . Yeo et al .…”
Section: Most Electrospun Polymers Used For Bone Regenerationmentioning
confidence: 99%
“…Electrospinning has also been successfully combined with other scaffold fabrication technologies with optimal outputs for various clinical targets. Electrospinning for example, combined with freeze‐dried materials and bone marrow stem cells enhanced osteochondral regeneration with improved compressive moduli in a rabbit model . Bimodal and multiphasic scaffolds can be fabricated using electrospinning and additive manufacturing .…”
Section: Electrospinningmentioning
confidence: 99%